Therapeutic effect of Yinhuapinggan granules mediated through the intestinal flora in mice infected with the H1N1 influenza virus - Yang, Can; Chen, Jing; Zhou, Huifen; Zeng, Di; Wan, Haitong; Yang, Jiehong (Frontiers in Microbiology, 2024)
Objective In this study, we examined the therapeutic effects of Yinhuapinggan granules (YHPGs) in influenza-infected mice. We also examined how YHPGs affect the composition of the intestinal flora and associated metabolites. Methods We used the nasal drip method to administer the influenza A virus (IAV) H1N1 to ICR mice. Following successful model construction, the mice were injected with 0.9% sterile saline and low (5.5 g/kg), medium (11 g/kg), and high (22 g/kg) doses of YHPGs. The pathological changes in the lungs and intestines were evaluated by gavage for 5 consecutive days. Detection of sIgA, IL-6, TNF-α, INF-γ, and TGF-β cytokine levels in serum by enzyme-linked immunosorbent assay. Real-time fluorescence quantitative polymerase chain reaction and Western blot were used to measure the mRNA and protein expression of the tight junction proteins claudin-1, occludin, and zonula occludens-1 (ZO-1) in the colon. To assess the influence of YHPGs on the intestinal microbiota, feces were obtained from the mice for 16s rRNA sequencing, and short-chain fatty acids (SCFAs) were measured in the feces. Results By reducing the production of pro-inflammatory cytokines and increasing the relative expression of claudin-1, occludin, and ZO-1 in colon tissues, YHPGs had a protective effect in tissues from the lungs and colon. When YHPGs were administered to mice with IAV infection, the relative abundance of Lactobacillus, Coprobacillus, Akkermansia, Prevotella, Oscillospira, and Ruminococcus increased, whereas the relative abundance of Desulfovibrio decreased. Conclusion The therapeutic mechanism of YHPGs against IAV infection in mice may be underpinned by modulation of the structural composition of colonic bacteria and regulation of SCFA production.